2014
DOI: 10.2298/vsp1406542j
|View full text |Cite
|
Sign up to set email alerts
|

Resection or radiofrequency ablation of colorectal liver metastasis

Abstract: This study shows that the patients with solitary hepatic colorectal cancer metastases should be considered for hepatic resection whenever it is feasible, because this procedure provides superior long-term survival as compared to radiofrequency ablation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…5) [13, 30, 31, 3335, 37, 39, 45, 46]. Pooling of the results showed that RFA was associated with an inferior OS (HR = 1.78; 95%CI 1.35–2.33)).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5) [13, 30, 31, 3335, 37, 39, 45, 46]. Pooling of the results showed that RFA was associated with an inferior OS (HR = 1.78; 95%CI 1.35–2.33)).…”
Section: Resultsmentioning
confidence: 99%
“…Five articles allowed for pooling of OS results for solitary metastases. Again, RFA was associated with a less favourable outcome (HR = 1.77; 95%CI 1.18–2.65) [ 31 , 33 35 , 39 ]. The corrected odds ratio as reported by Aloia et al also showed better results for PH alone (odds ratio 3.22; 95%CI 1.74–5.96) [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 1060 patients were treated for CRLM with the use of RFA and 1817 patients with hepatic resection. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] Quality assessment Quality assessment is shown in eTable 2 with 16 of the 20 studies having a score of at least 6/9 as per the NOS grading. [23][24][25][26][27]29,30,[32][33][34][35][37][38][39]41,42 Studies were downgraded because patients who received resection were not selected from the exact same population as patients who received RFA.…”
Section: Study Selectionmentioning
confidence: 99%
“…Three studies were additionally downgraded because they did not provide a description of how different outcomes were assessed, leaving a grade of 5 in the scale. 31,36,40 One study only had a grade of 3, because it was a seminar which only showed results without mentioning in detail the methods. 28…”
Section: Study Selectionmentioning
confidence: 99%
“…Several studies revealed that complications were significantly more common after surgery compared to RFA (relative risk [RR] = 0.47; 95%CI 0.28–0.78) [ 22 29 , 59 , 64 66 ]. Two studies reported serious adverse events in 21–28% after surgery vs 13–37% in the surgery + ablation group [ 18 , 24 ].…”
Section: Discussionmentioning
confidence: 99%